Novel evaporative cooling systems for building applications - Musa, Mu'azu (2009)
The technology and applications of evaporative cooling to provide human comfort in buildings is not new and has been used in different places based on different methods and materials. Conventional air conditioning systems overshadowed the application of evaporative cooling for buildings despite their ozone layer depletion. Evaporative cooling using porous ceramic evaporators were experimentally investigated. Encouraging results in terms of temperature reduction and cooling effectiveness were reported. In this work also thermoelectric unit was integrated in to the evaporative cooling system containing porous ceramic evaporators. The warm inlet air cooled in the evaporative cooling chamber was passed over the hot-side fins of the thermoelectric cooling device to act as a better heat sink. Typical test results showed that the cold side temperature of thermoelectric unit was 5Deg.C lower and the hot side was 10Deg.Clower, respectively when operated on the wet and dry porous ceramics evaporative cooling chamber. Direct evaporative cooling is often associated with the rise in relative humidity which may result in uncomfortable feeling due to unwanted increase in moisture. Indirect evaporative cooling offers a solution but still requires improvements in the effectiveness. There is also need for using cheap and readily available materials for the construction, requiring simple fabrication technology without very complex engineering infrastructure. Most widely used common fibrous materials have very limited capillary effect. So a periodic water spray system with an automatic control is required for running the cooler which adds to the power consumption, rise in operation costs as well as construction and operational difficulties. As a compromise using horizontal arrangement was considered. Use of pump for supplying water required to moisten the evaporative cooling surface was eliminated. The system was constructed and tested under varying temperature, relative humidity and air flow rates. Results showed significant temperature reduction accompanied with acceptable increase in relative humidity. Temperature drop of 6-10Deg.C between the inlet and outlet temperatures of the product or supply air was recorded. Increase in relative humidity of the supply air was 6 - 10% less than the working air. Application of this novel system was demonstrated in the parasol self-cooling arrangement. The fibre tube vaporative cooler has the potential of cooling a building space to the acceptable comfort limits. The application of porous ceramics for building space cooling, integrating the system to be used as a heat sink and the use of horizontal fibre tubes for evaporative cooling are all novel ideas in this field of research. Other novel features also include the ability to minimise energy consumption by eliminating common methods of continuous water circulation.